1998
DOI: 10.1038/33176
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oxytocin receptor function by direct binding of progesterone

Abstract: The steroid hormone progesterone (P4) is essential for establishing and maintaining pregnancy in mammals. One of its functions includes maintenance of uterine quiescence by decreasing uterine sensitivity to the uterotonic peptide hormone oxytocin. Although it is generally held that steroid hormones such as P4 act at a genomic level by binding to nuclear receptors and modulating the expression of specific target genes, we show here that the effect of P4 on uterine sensitivity to oxytocin involves direct, non-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
217
6
8

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(245 citation statements)
references
References 22 publications
14
217
6
8
Order By: Relevance
“…In addition, differences in PKC-dependent effects may be brought about by heterogeneity in the expression of other proteins that interact or associate with the GABA A receptor from the intracellular side (19-21). Progesterone(-metabolites) might prevent binding of oxytocin to its receptor (22). However, in such a scenario, activation of PKC, thereby bypassing the activation of postsynaptic oxytocin receptors, would still induce the suppression of the GABA A receptor, even in the presence of 3␣-OH-DHP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences in PKC-dependent effects may be brought about by heterogeneity in the expression of other proteins that interact or associate with the GABA A receptor from the intracellular side (19-21). Progesterone(-metabolites) might prevent binding of oxytocin to its receptor (22). However, in such a scenario, activation of PKC, thereby bypassing the activation of postsynaptic oxytocin receptors, would still induce the suppression of the GABA A receptor, even in the presence of 3␣-OH-DHP.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, OXT has been found to increase the intensity of orgasm and contentment after copulation (Behnia et al, 2014) and to reduce arousal induced by the imagination of sexual infidelity (Preckel et al, 2015). Peripheral estradiol and progesterone levels were found to be altered in women using HC and therefore a potential mechanism could be related to the direct binding of progesterone to OXTRs, thereby inhibiting OXTR functioning (Grazzini et al, 1998). Of note, an estradiol treatment in mice and rats results in a several-fold increase in OXTR mRNA in the brain (Quinones-Jenab et al, 1997;Young et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been shown that OXT increased the arousal induced by infant photos in nulliparous women (Rupp et al, 2013) and promoted responsiveness to infant crying and laughter by reducing activation in anxiety-related neural circuits (Riem et al, 2011(Riem et al, , 2012. Clearly, OXT effects in women may vary as a function of steroid hormones, which influence plasma levels of the peptide (Chiodera et al, 1991), regulate the expression of the OXTR gene (Quinones-Jenab et al, 1997) and affect OXTR function through a non-genomic mechanism (Grazzini et al, 1998). In fact, millions of women around the world use steroidbased hormonal contraception (HC) as an effective way of birthcontrol (Alkema et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ER is the primary target for chemoprevention and endocrine therapy, providing prognostic and predictive information of tumor response to endocrine treatment (21). However, several reports indicate steroid action in cells lacking classic receptors (22,23). These findings led to the identification of membrane binding elements, considered as new steroid hormone targets (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%